2019
DOI: 10.1186/s11658-018-0131-z
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-221 promotes cutaneous squamous cell carcinoma progression by targeting PTEN

Abstract: Background Cutaneous squamous cell carcinoma (CSCC) is a common type of skin malignancy. MicroRNA-221 (miRNA-221) is a critical non-coding RNA in tumor initiation and progression. However, the molecular mechanisms of miRNA-221 in the development of CSCC remain unknown. This study investigated the expression of miRNA-221 in CSCC and its potential tumor biological functions. Methods MTT assay, colony assay, PCR, and Western blot were adopted. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 22 publications
4
30
0
Order By: Relevance
“…miR-221 is a miRNA closely relate to cancer, which can be processed into miR-221-3p or miR-221-5p to find the role of gene regulation. 9 Different from miR-221-3p, the researches on miR-221-5p are rare in recent years, and only a few researches have reported the effect of miR-221-5p. For example, a study 10 found that miR-221-5p acts as a tumor suppressor gene in prostatic carcinoma, but no research has been conducted on its role in gastric cancer and related mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…miR-221 is a miRNA closely relate to cancer, which can be processed into miR-221-3p or miR-221-5p to find the role of gene regulation. 9 Different from miR-221-3p, the researches on miR-221-5p are rare in recent years, and only a few researches have reported the effect of miR-221-5p. For example, a study 10 found that miR-221-5p acts as a tumor suppressor gene in prostatic carcinoma, but no research has been conducted on its role in gastric cancer and related mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Functional analyses show that miR-365 inhibits apoptosis by directly targeting BAX [44] and forcing the cell cycle progression by NFIB repression [42,43]. As shown in recent studies, miR-186, miR-221, miR-506, and miR-142-5p contribute to cSCC tumor growth [45][46][47][48][49]. miR-186 promotes proliferation and inhibits apoptosis by targeting RETREG1 [48] and APAF1 [46].…”
Section: Mirnas In Cutaneous Squamous Cell Carcinomamentioning
confidence: 80%
“…For example, miR-21 can promote the proliferation and migration of breast cancer via targeting LZTFL1, 26 and miR-221 can promote the proliferation of cutaneous squamous cell carcinoma by targeting PTEN. 27 In NSCLC, the expression of miR-221 and miR-10a were up-regulated, and their overexpression could accelerate the proliferation, migration and invasion of cancer cells. 28,29 Consistent with previous reports, 16,17 we confirmed that miR-122-5p was down-regulated in NSCLC tissues and involved in the progression of NSCLC as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%